1983
DOI: 10.2307/3281356
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Host Immune Responses by Fasciola hepatica: Responses of Peripheral Lymphocytes to Mitogens during Liver Fluke Infections of Sheep

Abstract: Fasciola hepatica infections of lambs (250 or 500 metacercariae) were shown to alter the proliferative responses of peripheral blood lymphocytes (whole blood culture) to mitogens at specific times postinfection (PI). Responses to concanavalin A (Con A) were significantly suppressed at weeks 4, 8, 10, and 11 PI whereas suppressed responses to phytohemagglutinin (PHA) occurred at weeks 4, 10, 11, and 16 PI. Only on weeks 4 and 6 PI were responses to pokeweed mitogen (PWM) suppressed. The fluke-induced modulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…This finding is indicative of a persistent immune suppression. All the above findings are in agreement with the findings of other studies of different host species that have included infected rats but that have been performed at earlier stages of infection [19][20][21][22][23][24][25][26]. The reason for this unresponsiveness is not yet known.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is indicative of a persistent immune suppression. All the above findings are in agreement with the findings of other studies of different host species that have included infected rats but that have been performed at earlier stages of infection [19][20][21][22][23][24][25][26]. The reason for this unresponsiveness is not yet known.…”
Section: Discussionsupporting
confidence: 82%
“…The decreased responses to mitogens were signi®cant both after primary infection (between 6 and 12 weeks PPI) and after secondary infection (between 2 and 6 weeks PSI). Decreased responses to mitogens have been reported in sheep after primary infections (Zimmerman et al 1983;Chauvin et al 1995), although a short-lived increased response to ConA was observed after secondary infections (Chauvin et al 1995). It has been suggested that parasite products may be responsible for the immunosuppression of PBL responses, and this may explain the failure of the hosts to develop resistance to F. hepatica.…”
Section: Discussionmentioning
confidence: 89%
“…Both humoral and cell-mediated immune responses appear to be important for resistance to F. hepatica, although cellular responses seem to be more relevant. Some mechanisms of immune modulation in F. hepatica infection have also been described in dierent hosts, aecting either antibody activity (Chapman and Mitchell 1982) or lymphocyte response (Zimmerman et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Food and water were available ad libitum. Sheep and buffaloes were selected for the ability of their lymphocytes to respond to concanavalin A (ConA), as described previously by Zimmerman et al (1983), in order to limit the dispersion of the cellular response.…”
Section: Animalsmentioning
confidence: 99%